Troyes/Augustobona, cité des Tricasses - Michel Kasprzyk; Cédric Roms; Anne Delor-Ahü; Cyril Driard (Gallia)
The archaeological investigations from the last decade gave several different perspectives of observation on the ancient town of Troyes/Augustobona. They seem to confirm the existence of a settlement at the end of the Iron Age, assigned to the Senones people, and prior to the Augustan town. They also show the growth of an orthonormal urban network at the end of August’s reign where the occupation features mainly belong to the La Tène tradition. The second half of the 1st c. AD saw the building of a probable periurban sanctuary, and the development of building methods from Mediterranean tradition.